Research perception from layout plan and facilities for government low cost housing in Klang Valley, Kuala Lumpur - Zulkifli, Nurul Hidayah; Abdullah, Fadzidah (2012)
In Malaysia, low cost housing development is undertaken by both the public and private sectors. During 1984, Kuala Lumpur Plan (KLSP) aimed to ensure that sufficient housing would be provided for all income groups in the city and that housing was properly distributed so that its residents could be properly served in terms of infrastructure, utilities and community facilities. Recently space standard for low cost housing in the Dinth Malaysia Plan for new projects have been revised from minimum of 650 square foot to 700 square foot per unit. The same space standard also applies to disabled unit. The objective of this research is to identify the minimum comfort size of PPR (Program Perumahan Rakyat) unit for both normal unit and disabled unit. Furthermore, to determine the suitable ratio for car parking in government low cost high-rise housing. Besides, this research will propose recommendation to improve the aspects of size of the space for both normal unit and disabled unit and car parking provision. These findings can help government and related agencies to better understand the current issues in low-cost housing from different perspectives. This will probably lead to improvements in the implementation of low-cost housing development in Malaysia.